KELAYAKAN VIDEO TUTORIAL PEMBUATAN NATA DE CORN PADA SUBMATERI PERAN BIOTEKNOLOGI KELAS XII SMA - Ningsih, Ningsih; Yeni, Laili Fitri; Wahyu, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Â AbstractThis research aims to know the video tutorials the feasibility for maked Â nata de corn on material role of biotechnology in class XII senior high school. The form of research used is quantitative with descriptive methods. First is making of video tutorial and the second is validation of the media. Data collecting tool used is the question form validation of the worthiness of video tutorials. Validation of the feasibility of the media carried out by 6 people validator. Video tutorials are categorized invalid based on the results of validation by 3 people media expert of 3.57 and 3 people expert material amounted to 3.70. So it can be inferred that video tutorials worth used as media of instruction.Keywords: Nata de Corn, , Role of Biotechnology, Student Response, Video tutorials, Worthiness